"Perfidy Afoot!" Connor, the IEA and the Loans Affair. (23rd June 2021) - Kellow, Aynsley; Carroll, Peter
Abstract: When the International Energy Agency (IEA) was established out of the Organisation for Economic Co‐operation and Development (OECD) in 1974, Australia was not among its founding members. Indeed, it was opposed to its formation and even contemplated voting in the OECD to block its establishment. A single negative vote under the "mutual agreement" rule would have done so. This paper, based on archival research, explores the reasons for this course of action and shows that the decision was linked to the resource nationalism at the time of Minister Rex Connor and his fear that supporting it might jeopardise his attempts to raise non‐equity finance in the Middle East. This article shows that this previously unanalysed decision was connected to what became known as the "Loans Affair" that brought about Connor's demise and contributed to the downfall of the Whitlam Government.